Evolution of the nutritional status of COVID-19 critically-ill patients: A prospective observational study from ICU admission to three months after ICU discharge. Issue 12 (December 2022) - Rives-Lange, C.; Zimmer, A.; Merazka, A.; Carette, C.; Martins-Bexinga, A.; Hauw-Berlemont, C.; Guerot, E.; Jannot, A.S.; Diehl, J.L.; Czernichow, S.; Hermann, B.
Summary: Background & aims: Malnutrition following intensive care unit (ICU) stay is frequent and could be especially prominent in critically ill Coronavirus Disease 2019 (COVID-19) patients as they present prolonged inflammatory state and long length stay. We aimed to determine the prevalence of malnutrition in critically ill COVID-19 patients both at the acute and recovery phases of infection. Methods: We conducted a prospective observational study including critically ill COVID-19 patients requiring invasive mechanical ventilation discharged alive from a medical ICU of a university hospital. We collected demographic, anthropometric and ICU stay data (SAPS2, recourse to organ support and daily energy intake). Nutritional status and nutritional support were collected at one month after ICU discharge (M1) by phone interview and at 3 months after ICU discharge (M3) during a specialized and dedicated consultation conducted by a dietitian. Malnutrition diagnosis was based on weight loss and body mass index (BMI) criteria following the Global Leadership Initiative on Malnutrition. Primary outcome was the prevalence of malnutrition at M3 and secondary outcomes were the evolution of nutritional status from ICU admission to M3 and factors associated with malnutrition at M3. Results: From march 13th to may 15th, 2020, 38 patients were discharged alive from the ICU, median [IQR] age 66 [59–72] years, BMI 27.8 [25.5–30.7] kg/m 2 and SAPS2 47 [35–55]. Thirty-three (86%) patients were followed up to M3. Prevalence of malnutrition increased during the ICU stay, from 18% at ICU admission to 79% at ICU discharge and then decreased to 71% at M1 and 53% at M3. Severe malnutrition prevailed at ICU discharge with a prevalence of 55% decreasing 32% at M3. At M3, the only factors associated with malnutrition in univariate analysis were the length of invasive mechanical ventilation and length of ICU stay (28 [18–44] vs. 13 [11–24] days, P = 0.011 and 32 [22–48] vs. 17 [11–21] days, P = 0.006, respectively), while no ICU preadmission and admission factors, nor energy and protein intakes distinguished the two groups. Only 35% of undernourished patients at M3 had benefited from a nutritional support. Conclusion: Malnutrition is frequent, protracted and probably underrecognized among critically ill Covid-19 patients requiring invasive mechanical ventilation with more than half patients still being undernourished three months after ICU discharge. A particular attention should be paid to the nutritional status of these patients not only during their ICU stay but also following ICU discharge.